Clinical features and severe outcome predictors of COVID-19 vaccine breakthrough infection among hospitalized patients: results from Egypt severe acute respiratory infections sentinel surveillance, 2021–2022 - Kandeel, Amr; Fahim, Manal; Deghedy, Ola; Alim, Walaa; Fattah, Mohammad Abdel; Afifi, Salma; Mohsen, Amira; Abdelghaffar, Khaled (BMC infectious diseases, 2023)
COVID-19 vaccines are effective against infections and outcomes; however, breakthrough infections (VBT) are increasingly reported, possibly due to waning of vaccine-induced immunity or emerging variants. Most studies have focused on determining VBT rate based on antibody levels. This study aims at describing clinical features, risks, time trends, and outcomes of COVID-19 VBT among hospitalized patients in Egypt. Data of SARS-CoV-2 confirmed patients hospitalized in 16 hospitals was obtained from the severe acute respiratory infections surveillance database, September 2021-April 2022. Data includes patients' demographics, clinical picture, and outcomes. Descriptive analysis was performed and patients with VBT were compared to not fully vaccinated (UPV). Bivariate and multivariate analyses were performed using Epi Info7 with a significance level < 0.05 to identify VBT risk factors. Overall, 1,297 patients enrolled, their mean age 56.7 ± 17.0 years, 41.5% were males, 64.7% received inactivated, 25.% viral vector, and 7.7% mRNA vaccine. VBT was identified in 156(12.0%) patients with an increasing trend over time. VBT significantly was higher in (16-35 years) age, males, in those who received inactivated vaccine compared to corresponding groups of UPV (14.1 vs. 9.0%, p < 0.05 and 57.1 vs. 39.4%, p < 0.001 and 64.7 vs. 45.1, p < 0.01 respectively). Whereas receiving mRNA vaccine was significantly protective against VBT (7.7 vs. 21.6%, p < 001). VBT patients tend to have shorter hospital stays and lower case fatality (mean hospital days = 6.6 ± 5.5 vs. 7.9 ± 5.9, p < 0.01 and CFR = 28.2 vs. 33.1, p < 0.01 respectively). MVA identified younger ages, male gender, and inactivated vaccines as risks for VBT. The study indicated that COVID-19 vaccines significantly reduce hospital days and fatality. VBT trend is on the rise and males, young ages, and inactivated vaccine receivers are at higher risk. Caution regarding relaxation of personal preventive measures in areas with higher or increasing incidences of COVID-19, particularly for the at-risk group even if they are vaccinated. The vaccination strategy should be revised to reduce VBT rate and increase vaccine effectiveness.